Individual, environmental, and programmatic determinants of effective severe wasting treatment among children 6-59 months old in Afghanistan and Mali - Boyd, Erin. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: Patrick Webb.; Committee: Beatrice Rogers, and Kenneth Chui.; Keywords: Nutrition, and Public health.